A novel ''donor-two-acceptor'' type fluorophore-based probe for fast detection and intracellular imaging of nitroreductase. (January 2017) - Li, Dandan; Xu, Yuqiong; Zhou, Nannan; Liu, Jianxu; Wang, Rui; Cheng, Tao; Tang, Yun; Zhu, Weiping; Xu, Yufang; Qian, Xuhong
Abstract: By fusion of HBT and hemicyanine, we have designed a novel donor-two-acceptor type fluorophore (HHC ) as a platform for the detection of different kinds of guests.HHC displays an emission at 580 nm in aqueous solution and two emission bands at 450 nm and 616 nm as a result of the donor-two-acceptor feature with the existance of CTAB. The fluorescence ofHHC may be readily modulated by protection/deprotection of its electron-donating hydroxyl group and response different guests. As an example, we introduced p-nitrobenzyl group, which is sensitive to Nitroreductase (NTR), to the hydroxyl group ofHHC and constructed a novel selective and sensitive fluorescence probeHHCP for fast detection and intracellular imaging of nitroreductase. Graphical abstract: By fusion of HBT and hemicyanine, a novel donor-two-acceptor type fluorophore (HHC ) was developed as a platform for the detection of different kinds of guests. As an example, we introduced p-nitrobenzyl group, which is sensitive to Nitroreductase (NTR), to the hydroxyl group ofHHC and constructed a novel selective and sensitive fluorescence probeHHCP for fast detection and intracellular imaging of nitroreductase. Highlights: A novel donor-two-acceptor type fluorophore (HHC ) for the detection of different guests was designed and synthesized. The fluorescence ofHHC may be modulated by protection/deprotection of its electron donor and response different guests. A novel selective and sensitive fluorescence probeHHCP for fast detection and intracellular imaging of nitroreductase.